Molecular and acoustic evidence for large-scale underestimation of frog species diversity on New Guinea - Flavien Ferreira; Paul Oliver; Fred Kraus; Rainer Günther; Stephen Richards; Burhan Tjaturadi; Evy Arida; Amir Hamidy; Awal Riyanto; Wahyu Trilaksono; Christophe Thébaud; Antoine Fouquet (Frontiers of Biogeography)
Species are fundamental units in biology; however, information on species diversity and distribution remain scarce for most taxonomic groups, especially in tropical rainforests. Such knowledge gaps are particularly acute in amphibians, the most threatened group of vertebrates, in which new species continue to be described at a high rate. Herein, using molecular-based approaches, we provide estimates for species diversity of frogs (Anura) in New Guinea and nearby islands, one of the biologically most diverse regions of the world. We first characterised taxonomic and geographic sampling for all available mitochondrial DNA sequences from native frog species. This led us to identify important molecular sampling gaps in the western half of New Guinea that we partially filled by adding 534 new sequences (16S rRNA). Large territories remain uncharted, particularly in the westernmost part of the central cordillera of New Guinea. Using our 16S rRNA dataset, we then delimited Molecular Operational Taxonomic Units (MOTUs), a subset of which was bioacoustically analysed. From a total of 369 delimited MOTUs, we found that 190 could not be assigned to any taxon. Amongst these, 123 are represented by specimens collected in the western half of New Guinea and 19 were supported as distinct by bioacoustics, confirming that this portion of the island is home to many unrecognised species. Based on the estimated level of undescribed diversity in taxa and areas for which data are available, we extrapolate that New Guinea and neighbouring islands could host 800–1,200 frog species, with only 560 species described to date. Highlights We assembled the most comprehensive molecular dataset to date (16S rRNA) for frogs from New Guinea and neighbouring islands. We delimited 190 candidate species, of which 19 are supported by available bioacoustic data. We estimated the actual number of frog species on New Guinea and neighbouring islands to be between 800 and 1,200. Parts of New Guinea exhibit species-diversity levels comparable to similarly sized regions in Amazonia and Madagascar. Most unrecognised frog taxa in the region are likely confined to restricted geographical areas and, thus, likely sensitive to both land use and climate change.